REKOMENDASI PENINGKATAN PEMANFAATAN LAYANAN PERSALINAN NORMAL DI KLINIK PRATAMA RAWAT INAP RUMAH BERSALIN GRATIS RUMAH ZAKAT - Disrinama, Am Maisarah (2477 - 6165, 2016)
Intention of buying product or service is very important thing on purchasing stage. It depends on alternatives evaluation process on pre purchasing stage. K4 Pregnant woman has to decide the place to birth. The objective of this study is to create recommendation to increase Normal Labour on K4 Pregnant Women using Brand Image Analysis dan Three Stage Model of Service Consumption in Klinik Pratama Rawat Inap Rumah Bersalin Gratis Rumah Zakat. This research uses observasional analytic and prospective cohort. The primary data is collected two times, before and after delivery process. There are 54 respondents, whether all of K4 pregnant women with pregnancy age are more than 32 weeks. The samples were taken from March to August 2014. The result shows that some characteristics have relationship with purchasing decision. The recommendations consist of product, place, promotion, people, process, and physical evidence. Overall, the head of branch needs to fix the service for mother and child evaluation soon. Keywords: Brand image, Clinic, Normal birth, Three stage model of service consumption, Utilization of service.